A conceptual framework for Big Data Analytics adoption towards organization performance in Malaysia / Nur Khairiah Muhammad - Muhammad, Nur Khairiah (Faculty of Information Management, 2022)
The rise of Big Data has inspired business organizations to venture into Big Data Analytics, however academic research and empirical evidence about the business value remains scarce. This paper attempts to evaluate the readiness of Malaysia companies in taking advantage of Big Data adoption. The research finds a great interest about Big Data Analytics (BDA) solutions that fuel with sound decision-making and influence organizations into growth mindset. Big Data provides various advantages to organization that would seriously consider all its perspectives alongside its lifecycle in the pre-adoption or implementation phase. The research attempts to outline the different aspects of Big Data as a management practice to leverage the values of Big Data adoption in future organizations. As for the underpinning theory, the technology organization-environment (TOE) framework is chosen to describe the organizational adoption towards innovation decisions and Resource Based View to manage the upskill of the workforce. This is of great interest to researchers, professionals, and policy makers.